Reliability based inspection planning applications for offshore structures - Onoufriou, Toula (My University, 1996)
Experience from the development and application of reliability based inspection planning and optimisation methodologies on a range of offshore structures is discussed in this paper. A series of studies are discussed which demonstrate the progressive application from fixed platforms to floaters and jack-ups highlighting the particular methods that need to be adopted for each platform type. While the basic methodology is common in all cases there are a number of considerations specific to each type relating to their structural form, operational conditions and loading history which need to be taken into account when applying these techniques. The benefits obtained from the application of these methods are discussed with relevant example applications. Important trends and key parameters in this type of analysis are highlighted through the results of relevant parametric sensitivity studies. Areas where further work is needed to advance these applications are also highlighted and discussed in this paper.
Keywords: Risk management; Safety engineering; Offshore oil